Human Respiratory Syncytial Virus: Infection and Pathology - Bohmwald, Karen; Espinoza, Janyra A.; Rey-Jurado, Emma; Gómez, Roberto S.; González, Pablo A.; Bueno, Susan M.; Riedel, Claudia A.; Kalergis, Alexis M. (Seminars in Respiratory and Critical Care Medicine, 2016)
The human respiratory syncytial virus (hRSV) is by far the major cause of acute lower respiratory tract infections (ALRTIs) worldwide in infants and children younger than 2 years. The overwhelming number of hospitalizations due to hRSV-induced ALRTI each year is due, at least in part, to the lack of licensed vaccines against this virus. Thus, hRSV infection is considered a major public health problem and economic burden in most countries. The lung pathology developed in hRSV-infected individuals is characterized by an exacerbated proinflammatory and unbalanced Th2-type immune response. In addition to the adverse effects in airway tissues, hRSV infection can also cause neurologic manifestations in the host, such as seizures and encephalopathy. Although the origins of these extrapulmonary symptoms remain unclear, studies with patients suffering from neurological alterations suggest an involvement of the inflammatory response against hRSV. Furthermore, hRSV has evolved numerous mechanisms to modulate and evade the immune response in the host. Several studies have focused on elucidating the interactions between hRSV virulence factors and the host immune system, to rationally design new vaccines and therapies against this virus. Here, we discuss about the infection, pathology, and immune response triggered by hRSV in the host.
Keywords: human respiratory syncytial virus; virulence factors; innate immune response; adaptive immune response; extrapulmonary manifestations; central nervous system